The message of Chronicles one church, one faith, one Lord - Wilcock, Michael (Leicester, UK IVP, 1987)
Includes bibliographical references.
"The Bible Speaks Today series has been placed in the Emmaus Bible College Library in memory of Gordon W. Craig, 1926-1990"
Keywords: Bible. O.T. Chronicles -- commentaries